Aplikasi PCO Plus pada Tanah Bekas Tambang Batu Bata Merah terhadap Serapan P, Ca dan B serta Fruitset Cabai Merah Besar (Capsicum annuum L.) - Stefina Liana Sari; Rija Sudirja; Emma Trinurani Sofyan (Fakultas Pertanian Universitas Padjadjaran, 2017)
ABSTRACTApplication of liquid organic fertilizer formula plus on degraded soil to improve the productivity of the land and chili (Capsicum annuum L.) productionSoil exploitation in large numbers occurred in the District Wanaraja of Garut Regency. Excavation of soil more than 2 meters from the top layer for the manufacture of red bricks has exceeded the ability of the soil to re-establish its structure. So that the soils, which were agricultural lands, can be classified as degraded soils with less fertility and chemical properties. Lans reuse for agriculture requires adequate recovery and fertilizer input. This study aimed to determine the formula of LOF (liquid organic fertilizer) plus used with NPK compound fertilizer on degraded soil to improve the soil productivity. The design used was a Simple Randomized Block Design (RBD) by 10 combinations of LOF plus treatment with NPK compound fertilizer as follows: A = Control (degraded soil, no fertilizer), B = 0% LOF + 1 NPK, C = 0.25% LOF + 1 NPK, D = 0.50% LOF + 1 NPK, E = 0.75% LOF + 1 NPK, F = 1.00 % LOF + 1 NPK, G = 0.5% LOF + 3/4 NPK, H = 0.5% LOF + 1/2 NPK, I = 0.5% LOF + 1/4 NPK, J = 0.5 LOF + 0 NPK, and K = 1 NPK of normal soil that all replicated three times. The results showed that the degraded soil of red bricks required concentration of LOF above 0.5% to 1% when applied with 1 dose of standard NPK. It is able to balance the uptake of nutrients P, Ca, and B and percentage of fruitset in chili commodities equivalent to normal soil.Keywords: Chilli, Liquid Organic Faertilizer (LOF), NPK, Soil degrededABSTRAKEksploitasi tanah dalam jumlah yang besar terjadi di Kecamatan Wanaraja, Kabupaten Garut. Terjadinya penggalian tanah lebih dari 2 meter dari lapisan atas untuk pembuatan batu bata merah melampaui kemampuan tanah untuk membentuk struktur tanah kembali, sehingga tanah-tanah yang sebelumnya merupakan tanah pertanian ini dapat digolongkan menjadi tanah terdegradasi dengan sifat kimia kurang subur dan pemanfaatan kembali untuk pertanian memerlukan pemulihan dan input pupuk yang cukup. Penelitian ini bertujuan untuk mengetahui formula pupuk cair organik (PCO) plus yang digunakan bersama NPK pada tanah terdegradasi guna meningkatkan kembali produktvitas tanahnya. Rancangan yang digunakan adalah RAK sederhana dengan 10 kombinasi perlakuan PCO plus bersama NPK yaitu A = Kontrol (tanah terdegradasi, tanpa pupuk), B = 0% PCO + 1 NPK, C = 0,25% PCO + 1 NPK, D = 0,50% PCO + 1 NPK, E = 0,75% PCO + 1 NPK, F = 1,00% PCO + 1 NPK, G = 0,5% PCO + 3/4 NPK, H = 0,5% PCO + 1/2 NPK, I = 0,5% PCO + 1/4 NPK, J = 0,5 PCO + 0 NPK, dan K = 1 NPK tanah normal. Semua perlakuan diulang tiga kali. Hasil penelitian menunjukkan bahwa tanah terdegradasi bekas tambang batu bata merah memerlukan konsentrasi PCO di atas 0,5% sampai dengan 1% apabila diaplikasikan bersama 1 dosis NPKstandar. Hal ini mempu mengimbangi serapan hara P, Ca, dan B serta persen fruitset pada komoditas cabai setara dengan tanah normal.Kata Kunci: Cabai, NPK, Pupuk Cair Organik (PCO), Tanah terdegradasi